Current perspectives on the occurrence of Q fever: highlighting the need for systematic surveillance for a neglected zoonotic disease in Indian subcontinent. Issue 2 (20th December 2020) - Sahu, Radhakrishna; Rawool, Deepak Bhiwa; Dhaka, Pankaj; Yadav, Jay Prakash; Mishra, Sidharth Prasad; Kumar, Manesh; Vergis, Jess; Malik, Satyaveer Singh; Barbuddhe, Sukhadeo Baliram
Summary: Coxiellosis or Q fever is an important global occupational zoonotic disease caused by one of the most contagious bacterial pathogens – Coxiella burnetii, which ranks one among the 13 global priority zoonoses. The detection of C. burnetii infection is exhibiting an increasing trend in high‐risk personnel around the globe. It has increasingly been detected from foods of animal origin (including bulk milk, eggs, and meat) as well as tick vectors in many parts of the world. Coxiellosis is reported to be an important public health threat causing spontaneous abortions in humans and potential reproductive failure, which would result in production losses among livestock. Further, comprehensive coverage of the reports and trends of Q fever in developing countries, where this infection is supposed to be widely prevalent appears scarce. Also, the pathogen remains grossly neglected and underreported. Moreover, policymakers and funding agencies do not view it as a priority problem, especially in the Indian subcontinent, including Sri Lanka, Bhutan, Pakistan, Nepal, Bangladesh and Maldives. Here, we review the occurrence and epidemiology of the disease in a global context with special emphasis on its status in the Indian subcontinent.